23. Best Practices in Online Polling - Klaas, Jim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
This report summarizes major polling design principles and practices, with particular emphasis on those affecting the integrity of online polls in distance education (DE). Specific consideration is given to the statement of polling objectives, the design of good questions and response options, online poll format, motivation of the respondents, and poll pre-testing.